Simplified approach to validate constitutive model formulation of orthotropic materials undergoing finite strain deformation - Mohd Nor, Mohd Khir; Ma`at, Norzarina (Medwell Journals, 2016)
Modelling finite strain deformation including shockwave propagation in orthotropic materials requires an appropriate description of material behaviour within elastic and plastic regimes hence can be very complex. One of the real challenges of this work is to accurately validate each of the proposed formulation since the corresponding algorithm implementation normally involves more than thousand lines of code. The validation process must be systematically conducted by stages from simple to complex behaviours. In this paper, a new approach was developed and established to guide through this processes by referring to the newly constitutive model formulation applicable for finite strain deformation. The chosen constitutive model was implemented into the DYNA3D source code. The validation process was performed by conducting a series of a single element analysis of a uniaxial strain test and uniaxial stress test. The formulations of elastic isotropy, elastic orthotropy and elastic-plastic isotropy orthotropy (with and without hardening) of the proposed formulation were examined and validated against DYNA3D Material Types 10, 22 and 33 respectively in this stage. To really ensure the book-keeping of the proposed algorithm is clean and efficient the analysis on multiple elements analysis was performed. For this purpose, a Plate Impact test has been adopted on the elastic isotropy and elastic orthotropy analyses. The capability of the proposed formulation to capture the dependence of material under consideration on strain rate and temperature was finally investigated. A good agreement with respect to various flow stress conditions was obtained. The results then established the capability of the proposed formulation and its algorithm implementation before validation against the selected experimental tests can be conducted.